The Effect Of Customer Experience, Perceived Value And Trust On Customer Loyalty (Case Study On MSMEs Pottery In Pagelaran District, Malang Regency) - Sa’diah, Mufidatul; Alrasyid, Harun; Paramadina, Dita Roosemella (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract Customers in pottery Micro, Small and Medium Enterprises (MSMEs) in Pagelaran District, Malang Regency, are the focus of this study, which attempts to examine the impact of customer experience, perceived value, and trust on customer loyalty. Malang Regency, performance.Against the background of the important role of MSMEs in Indonesia's economy, this study identifies gaps in previous empirical studies that have not discussed customer loyalty in previous empirical studies that have not specifically discussed the relationship between these variables in the context of these variables in the context of pottery MSMEs. Customers of ceramic MSMEs in Malang Raya were given questionnaires to complete as part of the quantitative analysis study methodology. It is anticipated that the study's findings would shed further light on the variables influencing client loyalty and the role MSMEs play in the local economy. The study was carried out between November 2023 and January 2024. Keywords: Customer Experience, Perceived Value, Trust, Customer Loyalty